2022
DOI: 10.1002/bse.2975
|View full text |Cite
|
Sign up to set email alerts
|

The emerging driving force of inclusive green growth: Does digital economy agglomeration work?

Abstract: Inclusive green growth, which considers green growth, inclusive growth and growth, is a sustainable development model that aims to pursue the comprehensive and harmonious growth of humans, the economy, society, and the environment. Against the backdrop of the pandemic as well as sluggish economic development, the global economy is endowed with a driving mission that may affect inclusive green growth. This research primarily discusses the influence of digital economy agglomeration on inclusive green growth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(104 citation statements)
references
References 110 publications
(168 reference statements)
4
100
0
Order By: Relevance
“…In the short term (1-2 years), the contribution of computers to total factor productivity is almost zero. In the long term (more than 5 years), the contribution of computer investment to total factor productivity is more than five times that of investment [15]. Sánchez suggested that, in the improvement of digital economy, digital economy is a brand-new way to promote the circulation of commodities and the improvement of service industry.…”
Section: Related Workmentioning
confidence: 99%
“…In the short term (1-2 years), the contribution of computers to total factor productivity is almost zero. In the long term (more than 5 years), the contribution of computer investment to total factor productivity is more than five times that of investment [15]. Sánchez suggested that, in the improvement of digital economy, digital economy is a brand-new way to promote the circulation of commodities and the improvement of service industry.…”
Section: Related Workmentioning
confidence: 99%
“…As for the influencing factors of the digital economy, the literature covers a wide range, such as digital infrastructure [ 21 ], digital application [ 21 ], education [ 22 ], science and technology [ 23 ], etc. From the existing literature, there are great differences in the development levels of infrastructure, education, technology, and so on among Chinese cities, so there are great differences in the development of the digital economy.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of urban green development, the agglomeration of the digital economy can not only alleviate regional energy consumption and environmental pollution but also optimize the industrial structure and human capital, thereby promoting the green development of the regional environment (Ren et al, 2022). In addition, the digital economy can significantly improve the regional green total factor energy efficiency by improving the level of economic growth, urbanization, and research and development (R&D) .…”
Section: Impact Of Digital Economy On Urban Human Settlement Environmentmentioning
confidence: 99%